Classroom Discussions as Distortions: Examining Discriminatory Teacher Practices. (March 2017) - Sosa, Teresa; Bhathena, Catherine D.
Ms. Mendez, English Department chair in a large urban high school, has noticed a persistent pattern in the practices of her colleagues. These practices tend to be racially insensitive and emphasize a noncritical view that does not attend to students' experiences and positions students from a deficit perspective. Realizing that such practices serve as social reproductions of racist and classist orientations that reproduce the existing social order, Ms. Mendez decided school leadership should be informed. However, she worries that the school's leadership will not work to enact change and instead will take her concerns lightly.